2017
DOI: 10.3390/f8060183
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Fine Roots of Pinus massoniana in the Three Gorges Reservoir Area, China

Abstract: Several studies have focused on fine roots characteristics because they provide a major pathway for nutrient cycling and energy flow in forest ecosystems. However, few studies have evaluated changes in fine root characteristics according to their diameter. Pinus massoniana forests are the main vegetative component in the Three Gorges Reservoir area and play an important role in providing forest resources and ecological services. Pinus massoniana fine roots were sorted into 0-0.5, 0.5-1, and 1-2 mm diameter cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…However, there have been few studies performed on fine-root decomposition and nutrient cycling of P. massoniana. In the two previous studies on the decomposition of fine roots [36,37], the results regarding the regularity of decomposition do not agree. It is possible that arbitrary diameter cutoffs may mask decomposition heterogeneity within fine-root branching systems [28].…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…However, there have been few studies performed on fine-root decomposition and nutrient cycling of P. massoniana. In the two previous studies on the decomposition of fine roots [36,37], the results regarding the regularity of decomposition do not agree. It is possible that arbitrary diameter cutoffs may mask decomposition heterogeneity within fine-root branching systems [28].…”
Section: Introductionmentioning
confidence: 63%
“…The roots initially had a higher C:N ratio (low-N concentration) than microbes, but N immobilization from exogenous N is required to balance the microbial C:N ratio [32,40]. In the later stages of decomposition (days 120-360) when the C:N ratio reached critical values (35)(36)(37)(38)(39)(40), root residual N began to show the opposite trend regarding immobilization or release (Figures 2b and 3). These results agree with those from a previous meta-analysis of~2800 observations which reported that the critical value was from 67 to 77 during plant litter decomposition [40].…”
Section: Discussionmentioning
confidence: 98%
“…2f), which is inconsistent with previous research (He et al 2008). This inconsistency might be caused by the roots not being classi ed into more ne classes, as ne roots (diameter < 2 mm) were not evaluated separately, because ne roots have higher N and P nutrient concentrations than coarse roots (Shen et al 2017). Previous studies have proposed that a leaf N:P ratio < 14 indicates N limitation, while a N:P > 16 indicates P limitation (Koerselman and Meuleman 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Fine roots are primarily responsible for nutrient and water acquisition from the soil [45,53,54]. The relationships of fine root dynamics and soil temperature, moisture, and nutrients have been widely reported, but the results of these studies are not consistent [20,[55][56][57][58][59].…”
Section: Correlations Of Frb and Soil Factors In Response To Thinningmentioning
confidence: 99%